Análisis del caso No. 17282-2017-03001 respecto al delito del enriquecimiento privado no justificado y su similitud con el delito de defraudación tributaria - Jaramillo Macas, Paula Renata (2024)
The crime of unjustified private enrichment, since it is a criminally relevant conduct, was incorporated into the catalog of crimes due to the great economic and financial damage that it resulted for the country; however, because it is a relatively new crime, its doctrinal and jurisprudential analysis has been very scarce, bringing consequences in its form of interpretation for both jurists, administrators of justice, tax administration and holders of public action. That is why this crime required an in-depth analysis to determine which characteristics are similar to other crimes in order to avoid, as far as possible, a poor adaptation of the norm. In this sense, it is important to emphasize that private enrichment is an independent crime, so its evaluation must be carried out from each of the elements that make up the criminal offense, which its governing verb is focused on obtaining as the object of action an increase in assets without any justification, characteristics similar to the crime of tax fraud. The present investigation aims to analyze sentence No. 17828-2017-03001 regarding the crime of unjustified private enrichment and its similarity with the crime of tax fraud with the objective of analyzing the improper application of the criminal type of private enrichment and the inconsistencies in its persecution from the holders of public criminal action. To do this, a mixed mythology was used: quantitative and qualitative, analyzing the existing legal errors in the adaptation of the conduct with the criminal type, and proceeded to present the rationale for the proposal to reform the Comprehensive Organic Penal Code, article 297 section. fifth crimes against the development regime.